The Impact of Mother's Knowledge, Attitudes, and Age During Pregnancy on the Incidence of Stunting in Families: A Cross-Sectional Study: Dampak Pengetahuan, Sikap, dan Usia Ibu Saat Hamil terhadap Kejadian Stunting di Keluarga: Studi Cross-Sectional - Any Zahrotul Widniah; Aulia Rahmi (Salando Health Journal, 2024)
Stunting is a global issue faced by communities worldwide due to its chronic impact on child health and development. This study aims to analyze the relationship between maternal knowledge, attitude, and age during pregnancy with stunting incidence in families in the Astambul Health Center work area in 2023. A descriptive-analytic study with a cross-sectional design was conducted. Using accidental sampling, 100 respondents were selected from a population of 448 mothers with toddlers. Data were collected via questionnaires and analyzed using univariate and bivariate methods with chi-square tests. Results indicated a significant relationship between maternal knowledge, attitude, and age during pregnancy and stunting incidence (p-value = 0.001). Health workers should provide nutrition education programs to enhance maternal knowledge and prevent stunting.